Evaluasi Kebijakan Revitalisasi Pasar Tradisional : Studi Pasar Akau Potong Lembu Kota Tanjungpinang - Jamhur Poti; Mahadiansar Mahadiansar (Kolaborasi : Jurnal Administrasi Publik, 2020)
Revitalizing traditional markets is a form of improving the quality of public space as a policy of the regional government in cooperation with local communities. The purpose of revitalizing traditional markets is not merely to improve the physical form of traditional markets but also to manage these traditional markets. The researcher raised a case study on the policy after revitalizing the Lembu Market, Tanjungpinang City, to what extent the policies that have been implemented before and after the market revitalization match the public's expectations, it is necessary to evaluate the programs that have been implemented. Researchers used policy evaluation techniques with a formal evaluation approach using Dunn 2018 theory. The research method used by researchers used library research, by carrying out a search of several library sources such as e-books, journals, websites, organizational reports, and other good documents. print and online relevant to the topic being evaluated. The results showed that the evaluation of the revitalization program for the beef slaughter market in the city of Tanjungpinang had not found the value of cross-impact analysis and discounting on the program so that the revitalization of traditional markets was only in the form of target mapping, value clarification and mapping of barriers that had become the impact of the revitalization policy of the traditional cattle slaughter market in Tanjungpinang City. The researcher also did not find Urgency in realizing the traditional market revitalization policy in order to change the characteristics of the market for the better.